Gender within the Pursuit of Doctoral Education - Efiritha Chauraya (Nordic Journal of African Studies)
This study investigates the challenges faced by female PhD students in the pursuit of their doctoral education in Zimbabwe. The study’s broad aim was to explore female PhD students’ experiences within their doctoral studies. The study sample was formed of 12 students and three deans of higher degree studies from three top-ranking universities providing doctoral education in Zimbabwe. Purposive sampling was employed to settle on the participants and data were solicited through one-to-one semi-structured interviews. Data revealed that more male than female students pursued PhD studies and that more male than female students completed their PhD studies within the stipulated period of study. Data also revealed a myriad of gendered challenges that female PhD students encounter on their doctoral education journeys. The significance of the study is its contribution to research on doctoral education in Zimbabwe in general, as well as to the deepening of knowledge on the various challenges females pursuing PhD studies face.